ELUCIDATION OF NUTRITIONAL, PHYTOCHEMICAL AND PHARMACOLOGICAL ACTIVITIES OF TEUCRIUM POLIUM L GROWN IN LIBYA - R. Alghazeer1; S. Elgahmasi; E. Abdullah; O. Ahtiwesh; E. Althaluti; G. Shamlan; W. S. Alansari; A. A. Eskandrani (Journal of Animal and Plant Sciences, 2021)
Consumption of plant compounds play a crucial role in promoting health by improving the nutritional value of diet and preventing several chronic conditions such as cancer, cardiovascular, diabetes and neurological diseases. The current work aimed to analyse qualitatively and quantitatively the stem and leave extracts of Teucrium polium L.(Lamiaceae) grown in Libya for proximate, nutritional and phytochemical constituents as well as their biological properties. Methanolic extracts of leaves and stems were employed to evaluate their content of some of the primary and secondary compounds by several standard methods using a spectrophotometer. Additionally, the antioxidant properties of extracts were assessed using various in vitro systems including 1,1- diphenyl-2-picrylhydrazyl (DPPH), nitric oxide (NO) radicals scavenging ability, Lipid peroxidation activity, phosphomolybdenum reduction, and reducing power activity at different concentrations (6.25 to 100 mg/ml). Moreover, the cytotoxic effect of extracts was tested by measuring the Hemolytic activity against human red blood cells (hRBCs) while the anti-inflammatory was investigated by measuring the Inhibition of albumin denaturation. Results showed that the leaves had a higher concentration of carbohydrates, protein, fat, phenols, flavonoids, flavanols, tannins, catechins and coumarins, whereas the stems had a higher concentration of alkaloids. Correspondingly, the leaves displayed higher antioxidant properties (specifically, combatting lipid peroxidation) and a greater prevention of albumin denaturation than the stems. Both extracts inhibited hemolysis. Our findings provided valuable insight into the efficacy and applicability of plant compounds in the food and pharmaceutical industries.
Keywords: Teucrium polium; phytochemicals; antioxidant; hemolysis; anti-inflammatory